NEED ANALYSIS OF APPLYING E-LKPD BASED ON LIVEWORKSHEET NATURAL SCIENCE LEARNING SUBJECTS AT CLASS V ELEMENTARY SCHOOL - Fatima, Siti; Slamet, Adeng; Sumarni, Sri (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
One of the learning adaptation processes in the revolutionary era of 4.0 is digital and interactive-based student worksheets (LKPD). LKPDs are more innovative and can be packaged in online form or can be called Electronic Student Worksheets (E-LKPD). This paper aims to conduct a need analysis of E-LKPD based on live worksheets in science natural learning subjects at class V SD. The research was conducted at SDN 87 Palembang. Data collection uses a questionnaire with qualitative data. The data analysis technique used is descriptive analysis through data reduction, data presentation, conclusion, and verification. The data that need to be analyzed regarding the use of the teaching materials are the implementation of teaching and learning material through the evaluation system and the supporting factors. The research results of the need analysis imply that 46.9% answered that the learning method that was frequently used was discussion or question and answer. In addition, 84.4% of students answered that they had difficulty understanding natural science learning subjects in the class. A total of 78.1% of students stated that they really needed live worksheet-based E-LKPD teaching materials in the learning process in the class. Subsequently, 75% of students strongly agree that the use of the E-LKPD is equipped with interesting pictures, videos, audio, and questions. Hence, E-LKPD based on Liveworksheets can be used as an alternative electronic teaching material.